Estudo sobre corrosão em liga de aluminio com adicão de refinador de grão titânio boro - Becker, Camila Poma (2023)
The presence of aluminum in people's daily lives is increasingly common, being used in various areas, with a very high application in sectors that prioritize lightness and ease of heat dispersion. Thus, the performance of this material grows every year, and with the use of refiners in the composition of these aluminum alloys, it generates a comprehensive and greater possibility of improving its performance. For each objective proposed by the alloy, different refiner choices can be made, such as this study that focuses on studying the behavior of the percentage of each refiner in each alloy, providing a vision of the best application in the area of corrosion. The combination of titanium with boron in the alloy at a casting temperature of 650 °C studied proved to be an excellent combination, promoting the delay of corrosion in the material as well as greater difficulty in breaking the protective layer present on the aluminum surface, being the best result obtained from the refiner addition in the proportion of 5Ti1B for sample 2 compared to sample 1, without the refiner addition and the other two samples with the proportion of 3Ti1B and 5Ti2B, exposed to the electrolyte NaCl in the proportion of 3.5%.